2021
DOI: 10.1002/admt.202101031
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Wide Range and High Sensitivity Flexible Pressure Sensors with Ordered Multilevel Microstructures

Abstract: With the rapid development of healthcare and human‐machine interactions, there is a growing demand for flexible electronic skin to have a high sensitivity over a wide range. While current multilevel and hierarchical structures inspired by nature broadened the sensing range, the structural design still lacks systematic study. Hereby, an ordered multilevel microstructure is proposed, and the design strategy for performance regulation of piezoresistive pressure sensors is studied. Both microstructure height and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…However, when two or more stimuli act simultaneously, studies on the discrimination of stimuli are insufficient, and additionally, there are limitations due to mass production difficulties and low durability. Therefore, studies on structures having a high durability and mass production using microstructures of various shapes are in progress [ 299 , 300 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, when two or more stimuli act simultaneously, studies on the discrimination of stimuli are insufficient, and additionally, there are limitations due to mass production difficulties and low durability. Therefore, studies on structures having a high durability and mass production using microstructures of various shapes are in progress [ 299 , 300 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Metal materials also include various metal nanomaterials (nano-silver [ 47 , 48 ] and nano-gold [ 38 , 49 ]), metal thin-film materials (thin-film copper [ 50 ] and thin-film magnesium [ 51 ]), metal oxides [ 13 ], liquid metals [ 52 ], etc. Ordinary carbon materials include carbon nanotubes [ 53 , 54 ], carbon black [ 55 ], bio-derived carbon materials [ 56 , 57 ], etc. New two-dimensional materials include not only graphenes [ 40 , 58 , 59 , 60 ] and redox graphene [ 61 , 62 ] that have attracted much attention but also transition metal two-dimensional materials that have emerged in recent years (transition metal carbonitride Mxenes [ 63 , 64 ], two-dimensional transition metal chalcogenides TMDs [ 65 ]; conductive organic materials include PPy [ 66 , 67 ], PEDOT:PSS [ 68 , 69 ], etc.…”
Section: Fundamental Designs Of Flexible Pressure Sensorsmentioning
confidence: 99%
“…Due to the fact that the micro-nano-multilevel structure obtained from the outside world cannot control the distribution of the structure, some research groups process the required micro-nano-multilevel structure by artificial means. Zhou et al prepared flexible piezoresistive sensors with multilevel structures through low-cost laser marking technology, template technology, and spraying technology [ 55 ]. As shown in Figure 4 c, the desired ordered micro-nano-multilevel structure can be prepared by laser marking technology, and the sensing performance of the flexible sensor can be adjusted.…”
Section: Sensor Designs With Force-sensitive Interface Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multistage microstructures 24 and gradient pore structures 22 have been proposed to resolve the abovementioned problems. For example, the piezoresistive pressure sensor with a multilevel microdome structure designed by Geng et al 27 showed sensitivity (1.5−8.3 kPa −1 ) in a wide range (0.01−200 kPa). The multistage structure or gradient pore structure can deform gradually with increasing pressure and thus leads to a considerable sensitivity in a wide detection range.…”
Section: Introductionmentioning
confidence: 99%